2021
DOI: 10.1186/s12905-021-01210-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for failure of the levonorgestrel releasing intrauterine system in women with heavy menstrual bleeding

Abstract: Background This study was conducted to identify factors that are associated with failure of treatment using the levonorgestrel releasing intrauterine system (LNG-IUS) in women with heavy menstrual bleeding. Methods For this study, data of a cohort of women treated with an LNG-IUS was used. Women who suffered from heavy menstrual bleeding, aged 34 years and older, without intracavitary pathology and without a future child wish, were recruited in hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…41 This is a little higher than the 47% of women allocated to receive the LNG-IUS in the ECLIPSE trial who still had the LNG-IUS in situ at 5 years. 29 Younger age (< 45 years) and severe dysmenorrhoea have been identified as factors associated with discontinuation of the LNG-IUS within 2 years, although the overall rate of discontinuation in this cohort study was 46%, 42 higher than the 36% observed in the ECLIPSE trial at 2 years. An investigation of subsequent procedures following endometrial ablation and hysterectomy using data linkage in the entire Scottish health record system 23 achieved a median follow-up of 6.2 and 11.6 years, respectively.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…41 This is a little higher than the 47% of women allocated to receive the LNG-IUS in the ECLIPSE trial who still had the LNG-IUS in situ at 5 years. 29 Younger age (< 45 years) and severe dysmenorrhoea have been identified as factors associated with discontinuation of the LNG-IUS within 2 years, although the overall rate of discontinuation in this cohort study was 46%, 42 higher than the 36% observed in the ECLIPSE trial at 2 years. An investigation of subsequent procedures following endometrial ablation and hysterectomy using data linkage in the entire Scottish health record system 23 achieved a median follow-up of 6.2 and 11.6 years, respectively.…”
Section: Introductioncontrasting
confidence: 56%
“…The MMAS has a high degree of reliability and internal consistency, 45 has good content and construct validity, 47,48 is responsive 38,49 and is acceptable to respondents. 42,46,49,50 The MMAS seeks responses in relation to current HMB, so was anticipated to be not relevant to the vast majority of women at this 10-year follow-up and was presented as an optional section of the questionnaire to complete.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A recent investigation enrolled a cohort of 1714 subjects and followed them for 5 years, with 495 participants finishing the entire period. As shown in Figure 4 , the rate of amenorrhea among these women increased with time, and at the end of the five years, it almost reached 42% [ 129 ].…”
Section: Use In Abnormal Uterine Bleedingmentioning
confidence: 99%